The importance of the family history on the development of hypertension. - Abdul wahab, Taghred H. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: High blood pressure is one of several risk factors that can increase your chance of developing heart disease, astroke, and other serious conditions.